Plate 24. Part of Ward 4. - G.W. Bromley & Co. (Tufts Archival Research Center, 2005)
Part of Ward 4 included in G. W. Bromley & Co.'s 1928 Atlas of the city of Boston. Boston Proper and Back Bay from actual surveys and official plans.